From a Marxist Feminist Point of View : Essays on Freedom, Rationality and Human Nature - Holmstrom, Nancy, (Historical Materialism Book Series ;, 2024)
This book shows the fruitfulness of approaching key philosophical and political questions from a Marxist-feminist point of view. The idea is that different modes of production like capitalism and feudalism have structures -- 'relations of produc